A família, a empresa e o Comando : as faces do PCC em Minas Gerais - Douglas Eustáquio da Silva Viana (2022)
The Primeiro Comando da Capital (PCC - First Command of the Capital) is uniquely organized in relation to other criminal groups, which hampers the development of a metaphor capable of explaining the group's functioning. The PCC consists of three faces, as proposed by Gabriel Feltran, based on how the collective manifests itself: a enterprise, with financial objectives; a military command, in order to face enemies and dominate territories and, finally, a brotherhood that has, as a beginning and end, the commitment of mutual support among the brothers. The objective of this research is to analyze how the PCC articulated the three faces in Minas Gerais in 2018 and whether this articulation was dependent on local dynamics. This research analyzed 435 hours of recordings of conversations among members of the PCC that were collected in a police investigation. Used as oral documents, the conversations were transcribed and cataloged for analysis. The research made it possible to identify how the local contexts influence the organizational dynamics of the PCC in the territories, favoring or limiting the growth of the group. It was also possible to observe how the military and business characteristics of the PCC in Minas Gerais are articulated in function to the brotherhood that, in Minas Gerais territory, was the most significant expression of the Primeiro Comando da Capital.